Severely compromised supply of patch test allergens in Europe hampers adequate diagnosis of occupational and non-occupational contact allergy. A European Society of Contact Dermatitis (ESCD), European Academy of Allergy and Clinical Immunology (EAACI), European Academy of Dermatology and Venereology (EADV) task forces ‘Contact Dermatitis’ and ‘Occupational Skin Disease’ position paper - John, Swen Malte; Bonertz, Andreas; Zimmer, Julia; Aerts, Olivier; Bauer, Andrea; Bova, Maria; Brans, Richard; Del Giacco, Stefano; Dickel, Heinrich; Corazza, Monica; Crépy, Marie Noëlle; Gallo, Rosella; et al. (Contact Dermatitis, 2024)
Patch testing is the only clinically applicable diagnostic method for Type IV allergy. The availability of Type IV patch test (PT) allergens in Europe, however, is currently scarce. This severely compromises adequate diagnostics of contact allergy, leading to serious consequences for the affected patients. Against this background, the European Society of Contact Dermatitis (ESCD) has created a task force (TF) (i) to explore the current availability of PT substances in different member states, (ii) to highlight some of the unique characteristics of Type IV vs. other allergens and (iii) to suggest ways forward to promote and ensure availability of high-quality patch testing substances for the diagnosis of Type IV allergies throughout Europe. The suggestions of the TF on how to improve the availability of PT allergens are supported by the ESCD, the European Academy of Allergy and Clinical Immunology, and the European Academy of Dermatology and Venereology and intend to provide potential means to resolve the present medical crisis.
CRIS-Team Scopus Importer:2024-06-14
Keywords: allergen provocation test; European Pharmacopoeia; marketing authorisation; patch test; regulatory framework; skin test allergens; Type IV allergy